Bond Effects between Concrete and Steel Bar Using Different Diameter Bars and Different Initial Crack Width - Papa Niane Faye; Yinghua Ye; Bo Diao (Advances in Civil Engineering)
The importance of an accurate simulation of service conditions in the bond performance of reinforced concrete structures in coastal regions is highlighted. Four widths of initial crack of 0, 80, 150, and 210 microns were artificially made by inserting slice into bond specimens during concrete casting. Three bar diameters of 10 mm, 14 mm, and 18 mm were selected. At 28 days, the bond specimens were exposed to the environment of wet-dry cycles of seawater and atmosphere for another 90 days. The pull-out test was then conducted and chloride contents were tested at crack area along 40 mm depth. Results show that, for the specimen with 10 mm bar diameter, cracks width of less than 80 microns vanished rapidly during wet-dry cycles; for other specimens, cracks width of 100–150 microns decreased slightly. However the cracks of width more than 200 microns increased gradually; the chloride content decreased along the depth of concrete, and the chloride content increased as the widths of initial cracks increased or as the bar diameters increased. The ductility of bond specimens decreased as the diameter increased.